Pengembangan KIT Pembelajaran Dari Limbah Pada Materi Ikatan Kimia Untuk Meningkatkan Hasil Belajar Siswa - Khuzaimah Dasopang; Iis Siti Jahro (Universitas Negeri Medan, 2020)
The research with the title Development of Chemical Learning KIT from Waste on Chemical Bonding Materials to Improve Student Learning Outcomes in Class X high school aims to find out whether the KIT created can meet the eligibility standards of a KIT and can improve student learning outcomes. The population in this study were all students of class X SMA Budisatrya Medan. The sample used in this study was taken by purposive sampling of one class, namely class X MIA 1 as an experimental class that was taught using KIT learning media. The test instruments used in this study were 20 questions that have been tested valid. Based on the results of data analysis, the KIT Learning media made have met the eligibility standard and in the hypothesis test the data obtained from the calculation table obtained tcount= 13.90 while at 1.696 ttable, so the tcount is higher than the ttable value (tcount>ttable) then Ho rejected and Ha accepted so it can be concluded that the average chemistry learning outcomes of students taught using the Chemical Bond KIT learning media are made higher than the KKM value (by 70) ie the average posttest score of students is 84.29.